Reaching a consensus in multi-agent systems : a time invariant nonlinear rule - Saburov, Mansoor; Saburov, Khikmat (2013)
Multi-Agent Systems (MAS) have attracted more and more interest in recent years.Most researches in the study of discrete-time MAS,presented in the past few years,have considered linear cooperative rules. However, local interactions between agents are more likely to be governed by nonlinear rules. In this paper, we investigate the consensus of discrete-time MAS with time invariant nonlinear cooperative rules.Based on ourpresented nonlinear model, we showa consensus in the discretetime MAS. Our model generalizes a classical time invariant DeGrootmodel. It seems that, unlikea linear case, a consensus can be easily achieved a nonlinear case.